Report on RDA Italian translation - Simonetta Buttò (JLIS.it, 2018)
The Director of the Central Institute for the Union Catalogue of Italian libraries (ICCU) provides an updated overview on some of the several activities of the Institute, with special regard to the adaptation, translation and dissemination of international standards for bibliographic description among a variegated national library community.